Financial Sector Assessment : Malawi - World Bank (Washington, DC, 2013)
Malawi's financial system is small even by regional standards and bank dominated but with a variety of institutions and markets. The Malawian financial system consists of nine banks, two discount houses, one leasing company, eight insurance companies, four development finance institutions (DFIs), a young-but growing-microfinance industry, and a nascent capital market. Only 10 percent of Malawi's population has access to formal financial services, reflecting the high incidence of poverty, high degree of informality, and a high proportion of the population in rural areas. Malawi's financial system offers a variety of conventional financial services, concentrated on the short-term end of the yield curve, but with an increasing focus on down-market products. Significant ownership linkages within the financial system and with non-financial corporations pose challenges for governance and related party transactions.